The Influence of Store Atmosphere on Purchasing Decisions and Customer Satisfaction: A Case Study at the Pacific Restaurant, Blitar - Steve Anderson; Liem Gai Sin (AIBPM Publisher, 2020)
This study aims to analyze the effect of store atmosphere on purchasing decisions, the effect of store atmosphere on customer satisfaction, and the effect of purchasing decisions on customer satisfaction. This is a quantitative descriptive research conducted in Pacific Restaurant, Blitar. The population of this study is 100 as the respondents chosen by purposive sampling techniques. The data were analyzed with path analysis. The finds that: (1) There is a significant effect between store atmosphere on purchasing decisions; (2) There is a significant effect between store atmosphere on customer satisfaction; and (3) Purchasing decisions have a significant effect on customer satisfaction.